OP0007 Changes in Gene Expression and Inflammatory Proteins in Systemic Juvenile Idiopathic Arthritis Patients on Canakinumab Therapy. (10th June 2014) - Brachat, A.; Grom, A.; Wulffraat, N.; Brunner, H.; Quartier, P.; Brik, R.; McCann, L.; Ozdogan, H.; Rutkowska-Sak, L.; Schneider, R.; Gerloni, V.; Harel, L.; et al.
Abstract : Background: Interleukin (IL)-1β plays a key role in the pathogenesis of systemic juvenile idiopathic arthritis (SJIA). Canakinumab (CAN), a selective, fully human, anti-IL-1β monoclonal antibody, has been shown to be efficacious in the treatment of SJIA. 1 Objectives: To analyze gene expression and inflammatory proteins in blood of SJIA patients (pts) on CAN therapy.To identify biomarkers that predict clinical response to CAN treatment at baseline. Methods: Inflammatory protein biomarkers (IL-6; IL-18) and gene expression profiles of active SJIA pts (aged 2 to <20 yrs) before and during CAN or placebo treatment in 2 phase III trials were analyzed. Gene expression patterns were also compared to those in a healthy control group. Results: Gene expression : Changes upon CAN treatment at Day 3 were assessed. Using identical filtering criteria (≥2 fold, p≤0.05), no CAN responsive genes were found for placebo (n=9) or for CAN (n=11) treated pts that were non-responders (adapted pediatric [ACR]30 not achieved) at Day 15. In contrast, 171 probesets passed this filter for responder pts (n=52, ≥ACR30), all of whom received CAN. Strongly repressed genes included many inflammation- and innate immunity-related genes (eg, IL-1β, IL1R1, IL1R2, TLR1, TLR4, TLR5). A set of transcripts was identified for which high baseline expression levels predicted a majority of strong (≥ACR50) responders. However, baseline transcript levels of a second, smaller subgroup of strong CAN responders, were similar to ACR30 responders and non-responders which in turn resembled levels found in healthy controls (n=22). Upon CAN treatment, transcript levels largely returned to those resembling healthy controls in the majority of strong responders. Protein markers : IL-6 protein levels were reduced by Day 3 (-4.7x and -4.4x with p=0.002 and 0.0001, n=20 and n=51 for the respective 2 trials), and at Day 29 (-12.5x and -8.1x with p=0.01 and 0.00005, n=20 and n=65). Greater reduction at Days 3 and 29 was observed for pts with strong Day 15 ACR response. IL-18 levels were mostly unchanged until Day 29 and with only moderate reduction at Day 57. Conclusions: Canakinumab treatment resulted in a rapid, strong reduction of many pro-inflammatory transcripts and serum IL-6, while IL-18 levels showed a delayed, weaker reduction. A majority of strong treatment responders were characterized by a set of transcripts with high baseline levels which reduced to healthy subject levels with treatment while other strong responders did not show elevation of these transcripts at baseline, suggesting heterogeneity at the molecular level in SJIA pts benefitting from canakinumab. References: Ruperto N. et al. N Engl J Med 2012;367:2396-406. Disclosure of Interest: A. Brachat Shareholder of: Novartis, Employee of: Novartis, A. Grom Consultant for: Novartis, Roche, NovImmune, N. Wulffraat Grant/research support: AbbVie, Roche, Consultant for: Novartis, Pfizer, Roche, H. Brunner Consultant for: Novarits, Roche, Astrazeneca, Celgene, Pfizer, Janssen, UCB, GSK, BMS, Speakers bureau: Novartis, P. Quartier Grant/research support: AbbVie, Chigai-Roche, Novartis, Pfizer, Consultant for: Chugai-Roche, Novartis, Pfizer, Speakers bureau: Abbott/AbbVie, BMS, Chugai-Roche, Novartis, Pfizer, Servier, SOBI, R. Brik Grant/research support: Novartis, Consultant for: Novartis, L. McCann: None declared, H. Ozdogan Consultant for: Novartis, L. Rutkowska-Sak: None declared, R. Schneider Consultant for: Novartis, Roche, V. Gerloni: None declared, L. Harel: None declared, M. Terreri: None declared, K. Houghton: None declared, R. Joos: None declared, D. Kingsbury: None declared, J. Lopez-Benitez: None declared, S. Bek Employee of: Novartis, M. Schumacher Employee of: Novartis, M. Valentin Shareholder of: Novartis, Employee of: Novartis, H. Gram Employee of: Novartis, K. Abrams Shareholder of: Novartis, Employee of: Novartis, A. Martini Grant/research support: BMS, Centocor, GSK, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences: To Gaslini Hospital to support PRINTO research, Consultant for: BMS, Centocor, GSK, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences:To Gaslini Hospital to support PRINTO research, Speakers bureau: Abbott, BMS, Astellas, Boehringer, Italfarmaco, MedImmune, Novartis, NovoNordisk, Pfizer, Sanofi Aventis, Roche, Servier, N. Ruperto Grant/research support: Abbott, Astrazeneca, BMS, Centocor, Eli Lilly, Francesco Angelini, GSK, Italfarmaco, Novartis, Pfizer/Wyeth, Roche, Sanofi Aventis, Schwarz Biosciences, Xoma: to Gaslini Hospital, Speakers bureau: Astrazeneca, BMS, Janssen Biologics BV, Roche, Pfizer/Wyeth, D. Lovell Grant/research support: National Institutes of Health-NIAMS, Consultant for: Astra-Zeneca, Centocor, Amgen, Bristol Meyers Squibb, Abbott, Pfizer, Regeneron, Roche, Novartis, UCB, Forest Research Institute, Horizon, Johnson & Johnson, Speakers bureau: Novartis, Roche, N. Nirmala Employee of: Novartis DOI: 10.1136/annrheumdis-2014-eular.2320